A utilização da informação contábil na atividade pecuária do Estado do Rio Grande do Norte: um enfoque nos demonstrativos gerados para tomada de decisão - Souza, Domingos Carvalho de (2004)
This work deals with the cattle raising activity in Brasil, it´s importance for the stete of Rio Grande do Norte. A conceptual review is done regarding accounting information and considering it as an essencial input for economical and finantial decision making, related to the state cattle rainsing environment. It also aims to expose visions related to the role and the importance of Accounting as system that colects, treats and supplies managerial information. A brief historic of Accounting is done, emphasizing the Accounting Demonstration Structure and its use in the decision making process, as well as the contribution it has node for the cattle raising activity in Brazil. The research´s results show that accounting information is used partially in the finantial decision making process, and it is pointed out that the Inventory was the most relevant tool with 95,% of the cases, followed by the Income and Outlay reports with 85.0%,Production with 82,0% and Cost reports with 80,0%, the Demonstrative of the Cash Flow (DFC) with 82.5%, the Patrimonial Balance (PB) with 22.5%, and the Demonstrative of the Exercise Result (DER) with 20.0% of use. The research concludes that Accounting information is not throughly used in the economic and finantial decision making of the managers of cattle raising in the Rio Grande do Norte State, although, 95% of the sample consider then important. This may imply that there are diffilculties in measurement of the managerial decisions as well as the business whole